THE MARKETING OF SHEEP MEAT IN THE MUCIPAITY OF POMBAL-PB - Gama, Kallidiane Vaneska Mendes Fernandes; Soares, Rafael Farias; Sousa, Luci Cleide Farias Soares (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2012)
Abstract - The municipality of Pombal - PB and the surrounding region possesses one of the main economic activities and thus the sheep industry trade in sheep meat is broad. Thus, the aim with this work, follow and describe the marketing of sheep meat in the municipality of Pombal - PB. Interviews were conducted with the owners of stores and markets selling meat sheep in the city. We can see that they still have not herd sheep for cutting enough to meet local demand and establishments that sell meat sheep need to improve the sanitary conditions of their facilities. It is suggested a course of good food handling practices of animal origin for local merchants. Keywords: Sheep Meat, Supply, Sanitation.